Evaluation of a full-scale wastewater treatment plant with ozonation and different post-treatments using a broad range of in vitro and in vivo bioassays. (1st April 2022) - Kienle, Cornelia; Werner, Inge; Fischer, Stephan; Lüthi, Christina; Schifferli, Andrea; Besselink, Harrie; Langer, Miriam; McArdell, Christa S.; Vermeirssen, Etiënne L.M.
Highlights: 10 in vitro and 5 in vivo bioassays applied to evaluate ozonation and post-treatments. Ozonation showed significant beneficial effects on water quality of effluent. Selected bioassays showed additional improvement of water quality by post-treatments. Abstract: Micropollutants present in the effluent of wastewater treatment plants (WWTPs) after biological treatment are largely eliminated by effective advanced technologies such as ozonation. Discharge of contaminants into freshwater ecosystems can thus be minimized, while simultaneously protecting drinking water resources. However, ozonation can lead to reactive and potentially toxic transformation products. To remove these, the Swiss Federal Office for the Environment recommends additional "post-treatment" of ozonated WWTP effluent using sand filtration, but other treatments may be similarly effective. In this study, 48 h composite wastewater samples were collected before and after full-scale ozonation, and after post-treatments (full-scale sand filtration, pilot-scale fresh and pre-loaded granular activated carbon, and fixed and moving beds). Ecotoxicological tests were performed to quantify the changes in water quality following different treatment steps. These included standard in vitro bioassays for the detection of endocrine, genotoxic and mutagenic effects, as well as toxicity to green algae and bacteria, and flow-through in vivo bioassays using oligochaetes and early life stages of rainbow trout. Results show that ozonation reduced a number of ecotoxicological effects of biologically treated wastewater by 66 - 93%: It improved growth and photosynthesis of green algae, decreased toxicity to luminescent bacteria, reduced concentrations of hormonally active contaminants and significantly changed expression of biomarker genes in rainbow trout liver. Bioassay results showed that ozonation did not produce problematic levels of reaction products overall. Small increases in toxicity observed in a few samples were reduced or eliminated by post-treatments. However, only relatively fresh granular activated carbon (analyzed at 13, 000 - 20, 000 bed volumes) significantly reduced effects additionally (by up to 66%) compared to ozonation alone. Inhibition of algal photosynthesis, rainbow trout liver histopathology and biomarker gene expression proved to be sufficiently sensitive endpoints to detect the change in water quality achieved by post-treatment. Graphical abstract: Image, graphical abstract